COST OVERRUNS ON RAILWAY SIGNALLING PROJECT: QUALITATIVE CASE STUDY ON LRS COMPANY - Rustandi Rustandi; Ali Muktiyanto; Ceacilia Srimindarti (Jurnal Riset Bisnis dan Manajemen, 2022)
Railway is a mode of transportation that provides several advantages over other modes in terms of punctuality, capacity and energy efficiency. The signalling system is the main element of the railway which functions to ensure the safety of train travel. Several signalling construction projects carried out by LRS experienced cost overruns. It is necessary to conduct research to determine the causes of cost overruns, as the basis for the improvement process of Project Cost Management. The research was conducted using a qualitative case study method referring to the Miles & Huberman interactive model, with descriptive analysis. Data collection was carried out by triangulation including in-depth interviews, documentation, and FGDs. The selection of informants was carried out using purposive sampling method combined with snowball sampling method. Triangulation of data collection methods and triangulation of sources was carried out to increase the reliability of the research. The study found that the four factors most frequently mentioned by informants as the main causes of cost overruns, namely: Changes in scope; Extension of time; Weak of internal planning and Increase in material prices.